Erindring i Det Gamle Testamente - Carstens, Pernille (Dansk Teologisk Tidsskrift, 2013)
Literary texts are paths or tracks into cultural memory, not direct access to unmediated memory. Cultural memory studies are about how the past is mediated, how memory is produced and circulated. It is not about history “as such”. The Old Testament was created in periods of globalization. The writing is a piece of memory work meant for creation of national or local identity, and particularity in a global world. Memory as counter-activity is always present, focusing on the local, small tradition, the particular narrative, and creating its own way of coherence. Memories are not ready-prepared refl ections of the past. They are both eclectic and selective reconstructions. Remembering and forgetting the past refl ects the needs in the present. It is an active and ongoing, not predetermined process. Memory studies do not represent a coherent field, but are coming from different disciplines and discursive areas. It is an analytic instrument and a heuristic tool focusing the socio-cultural context.